Relationship Between Family Support And Blood Glucose Levels In Type 2 Diabetes Mellitus Patients In Mandai Public Health Center, Maros District, South Sulawesi Province - Puan Nusaputri Waetenrisompa; Arni Isnaini Arfah; Yani Sodiqah; Rachmat Faisal Syamsu; Abdul Mubdi Ardiansar (Jurnal EduHealth, 2024)
Diabetes Mellitus (DM) type 2 is a metabolic disease whose prevalence is increasing globally, including in Indonesia. Family support is known to help patients manage this condition through lifestyle changes and adherence to treatment. This study aims to determine the relationship between family support and blood glucose values in patients with type 2 DM, as well as to assess the relationship between medication adherence and blood glucose values. This research method uses a correlation analytic design with a cross-sectional approach. sectional. Data collection through questionnaires filled out by 32 type 2 DM patients. Hensarling Diabetes Family Support Questionnaire Scale (HDFSS) to assess family support and Morisky Medication Adherence Scale (MMAS-8) for medication adherence. Data analysis using Fisher's Exact Test to see the relationship between family support and blood glucose levels in type 2 diabetes mellitus patients and stratification analysis with Mentel haenszel. The results of the study found a relationship between family support and blood glucose values in patients with type 2 diabetes mellitus (p = 0.002; OR 24,000). The relationship between medication adherence and blood glucose values was not found to be significantly related (p = 0.265). The conclusion of this study is that family support significantly contributes to blood glucose values in patients with type 2 diabetes and medication adherence does not show a significant relationship to blood glucose values..